Fermiology of new charge-transfer salts, beta ''-(BEDT-TTF)(4)[(H3O)M(C2O4)(3)]center dot solvent where M = Ga, Cr and Fe - Coldea, A; Bangura, A; Ardavan, A; Singleton, J; Akutsu-Sato, A; Akutsu, H; Turner, S; Day, R (2004)
We report high-field magnetotransport measurements oil beta"-(BEDT-TTF)(4)[(H3O)M(C2O4)(3)], solvent, where M=Ga3+, Cr3+ and Fe3+ and solvent=C5H5N. In spite of their differing transition metal-ions, M, the three compounds exhibit similar magnetic quantum oscillation spectra superimposed on a positive magnetoresistance. At least four independent quantum oscillation frequencies have been identified, corresponding to two different hole and electron pockets of the Fermi surface which follow the rules of a compensated metal. Observation of the small pockets could be the result of the Fermi surface reconstruction induced by a possible density wave. The effective masses are very similar for different samples and for different pockets range between m(eff) approximate to 0.5 - 1.1 m(e) whereas the Dingle temperatures varies between T-D approximate to 1.4 - 4 K. At low temperature, the longitudinal magnetoresistance violates Kohler's rule, suggesting that the interlayer transport in these quasi-2D systems cannot be related to a single scattering time and that the disorder plays an important role.